The Impact of COVID-19 Restrictions on Online Sales of HIV Self-Test Kits and Implications for HIV Prevention: Analysis of Transaction Data from a Leading E-commerce Platform in China. (1st August 2022) - Luo, Ganfeng; Su, Lingyun; Hu, Yuqing; Zhou, Yiguo; Sun, Yinghui; Feng, Anping; Lin, Yi-Fan; Wu, Xinsheng; Zou, Huachun
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: The effect of the COVID-19 epidemic on HIV self-testing (HIVST) remains unclear. We aimed to quantify the impact of COVID restrictions on HIVST kit purchasing behaviors in mainland China. Methods: Deidentified transaction data were retrieved from a large online shopping platform. An interrupted time series model was constructed to examine the impact of COVID restrictions on the weekly number of anonymous customers purchasing HIVST kits, online orders, and purchased kits. Results: A total of 2.32 million individuals submitted 4.46 million orders for 4.84 million HIVST kits between January 7, 2016, and April 22, 2020. Compared with expected levels, assuming COVID-19 epidemic and related restrictions had not happened, the number of purchasers, orders, and kits decreased by an estimated 10, 500 (51.7%), 18, 000 (55.3%), and 18, 500 (54.9%) in the first week (January 23, 2020, to January 29, 2020) after COVID restrictions were implemented, respectively. As restrictions eased, the number of purchasers, orders, and kits increased by an average of 7.4%, 4.8%, and 4.9% per week, respectively. In the first week after COVID restrictions were lifted (April 9, 2020, to April 15, 2020), the number of purchasers returned to expected levels, whereas the number of orders and kits were still lower than expected levels. The impact of COVID restrictions on outcomes at the beginning of COVID restrictions and the increasing trends of outcomes were larger among those living in regions with higher COVID-19 incidence (eg, Wuhan city and Hubei province). Conclusions: Online sales of HIVST kits were significantly impacted by COVID restrictions, and HIVST kit purchasing patterns returned to expected levels after restrictions were lifted.